Forensic science education and training : a tool-kit for lecturers and practitioner trainers - Cassella, John P.; Maskell, Peter D.; Williams, Anna; Ohio Library and Information Network (Hoboken : Wiley, 2017)
A comprehensive and innovative guide to teaching, learning and assessment in forensic science education and practitioner training Includes student exercises for mock crime scene and disaster scenarios Addresses innovative teaching methods including apps and e-gaming Discusses existing and proposed teaching methods--;The book discusses existing and proposed methods for teaching theory, combined with hands-on practical exercises, and evaluates the current methodologies for assessing student and practitioner competencies--
Machine generated contents note: Foreword Brian Rankin Chapter 1: Forensic Science Education -- The Past and the Present In and Out of The Classroom John Cassella Chapter 2: Forensic Anthropology Teaching Practice Anna Williams Chapter 3: Considerations in using a Crime Scene House Facility for teaching and Learning David Rogers Chapter 4: Taphonomy Facilities as Teaching Aids Peter Cross and Anna Williams Chapter 5: Forensic Fire Investigation Richard Price Chapter 6: Digital Forensics Education Chris Hargreaves Chapter 7: A Strategy for Teaching Forensic Investigation with Limited Resources Janice Kennedy Chapter 8: Improving the PhD through provision of skills training for postgraduate researchers Ben Jones Chapter 9: Educational forensic e-gaming as effective learning environments for Higher Education students Jamie Pringle, Luke Bracegirdle and Jackie Potter Chapter 10: Virtual Anatomy Teaching Aids Kris Thompson and Anna Williams Chapter 11: Online Teaching Aids Anna-Maria Muller, L Taylor and Anna Williams Chapter 12: Simulation, immersive gameplay and virtual realities in Forensic Science Education Karl Harrison and Colleen Morgan Chapter 13: Training Forensic Practitioners In DNA Profiling Sue Carney Chapter 14: The Forensic Investigation of Sexual Offences: Practitioner Course Design and Delivery Sue Carney Chapter 15: The Use of High Fidelity Simulations in Emergency Management Training Graham Braithwaite Chapter 16: Police training in the 21st Century Mark Roycroft Chapter 17: The Design and Implementation of Multiple Choice Questions (MCQs) in Forensic Science Assessment Claire Gwinnett Chapter 18: The Future of Forensic Science Education John Cassella, Anna Williams and Peter D Maskell
Includes index
Includes bibliographical references and index.
Keywords: Forensic sciences